Serum gastrin levels in different stages of distal gastric carcinogenesis: Is there a role for serum gastrin in tumor growth? - Byung Chun Kim,; Sung Won Jung,; Jin Bae Kim,; A Rum Han,; Sung III Jang,; Sang Hoon Park,; Myung Seok Lee,; Jai Hoon Yoon,; Gwang Ho Baik,; Hyung Joo Jang,; Jung Han Kim,; Hyung Su Kim,; et al. (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Elevated levels of serum gastrin (SG) have been associated with tumorigenic effects in a number of gastrointestinal cancers. We decided to investigate the relationship between SG and gastric epithelial lesions. Materials and Methods: A total of 90 patients with gastric epithelial lesions (hyperplastic polyp, 12; adenoma, 41; early gastric cancer, 29; advanced gastric cancer, 8) were enrolled as the case group and 79 patients without epithelial lesions were enrolled as the control group. Results: Serum gastrin levels were significantly different between the case and control groups (p<0.001). A high SG level (>80 pg/mL), intestinal metaplasia, and a pepsinogen I/II ratio <3 were independently associated with an increased risk of epithelial lesions (odds ratio: 14.6, 9.4, and 4.1, respectively, p<0.05). SG levels in case subjects showed a unimodal distribution pattern as the disease progressed. The mean SG level was highest in those with hyperplastic polyps and then decreased significantly to the control level in the gastric cancer group. Higher SG levels in each disease category were not associated with increased tumor size, synchronicity, invasiveness, presence of lymph node metastasis, or a higher cellular proliferation index (p>0.05). Conclusion: An increased SG level was an independent and potent risk factor for gastric epithelial lesions. However, it does not seem to relate with distal gastric tumor growth. Serial decreases in SG levels should be considered a warning sign in index hypergastrinemic patients with no prior Helicobacter pylori eradication.